A planar eight‐way compact substrate integrated waveguide based radial power divider with broadband performance. Issue 3 (23rd November 2019) - Guha Mallick, Souma; Gande, Arun Kumar; Biswas, Bijit; Chatterjee, Sayan; Poddar, D. R.
Abstract: A compact broadband eight‐way substrate integrated waveguide (SIW) based radial power divider at C‐band is presented in the article. Bandwidth enhancement is achieved by employing planar impedance transformer consisting of an annular slot and circular patch at the input and output feed positions. The equivalent circuit analysis helps in the optimization of the annular slot and circular patch on the substrate. The proposed compact power divider has fractional bandwidth of 53.5% for 15 dB input return loss. Broadband characteristics are achieved without using any bulky mechanical arrangement for feed matching. It has a size of 0.72 λg 2 and the measured amplitude imbalance is within 0.5 dB at the center frequency of 6.6 GHz.